Physiotherapeutic treatments for malformations in myelomeningocele (Research, Society and Development, 2023)
The objective of the present study was to present physiotherapeutic interventions in malformations caused by myelomeningocele with a view to improving functional independence. Myelomeningocele, also known as spina bifida, is a severe congenital malformation of the spine, a pathology that occurs during the first four weeks of pregnancy. , resulting from a failure to close the neural tube, which may or may not result in spinal cord exposure. For this purpose, a search was carried out in the SciELO, Lilacs, Medline and Pubmed databases. The key words were used: Physiotherapy, Myelomeningocele and physiotherapeutic treatment, with the expected results of physiotherapeutic treatments for malformations in myelomeningocele. Physiotherapy plays a crucial role in the treatment of this pathology, contributing significantly to minimizing malformations and promoting improvements in activities of daily living. , therefore, by integrating physiotherapy into the care plan, it is possible to achieve positive results, promoting not only physical rehabilitation, but also providing well-being and autonomy to the individual affected by the pathology.